2012
DOI: 10.9738/cc84.1
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Trauma in Durban, South Africa: Factors Influencing Outcome

Abstract: Abdominal injury as a result of both blunt and penetrating trauma has an appreciable mortality rate from hemorrhage and sepsis. In this article, we present our experience with the management of abdominal trauma in Durban and investigate factors that influence outcome. We performed a prospective study of patients with abdominal trauma in one surgical ward at King Edward VIII Hospital in Durban over a period of 7 years, from 1998 through 2004. Demographic details, cause of injury, delay before surgery, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
35
1
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 31 publications
12
35
1
12
Order By: Relevance
“…5 The most common mechanism of blunt abdominal trauma evaluated in most studies and the present study were a car crash. 2,3,7,9,19,[22][23][24] In this study from 332 patients with blunt abdominal trauma, 290 cases (83.7%) had not any damage to any organ. Spleen and liver were equally the most injured organs.…”
Section: Data Collection Tools: Questionnairementioning
confidence: 69%
See 2 more Smart Citations
“…5 The most common mechanism of blunt abdominal trauma evaluated in most studies and the present study were a car crash. 2,3,7,9,19,[22][23][24] In this study from 332 patients with blunt abdominal trauma, 290 cases (83.7%) had not any damage to any organ. Spleen and liver were equally the most injured organs.…”
Section: Data Collection Tools: Questionnairementioning
confidence: 69%
“…In similar studies, blunt abdominal trauma was reported to be more common in men. 1,4,7,9 This is probably due to the outdoor activity of men.…”
Section: Data Collection Tools: Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…The liver, followed by the spleen are the most commonly injured abdominal organs in blunt abdominal injuries. In these injuries, shock, acidosis, transfusion requirement, presence of multiple organ injury, delay in treatment, presence of co-morbid diseases and high trauma sco-res are factors increasing mortality (3)(4)(5). Although there are studies reporting mortality rate as high as 25.8% (64 deaths in 248 trauma patients) for abdominal injuries, in general the mortality is 10% (3-5, 9).…”
Section: Discussionmentioning
confidence: 99%
“…These can be non-penetrating or penetrating when they pass through the peritoneal cavity. The epidemiology differ greatly by geographic region; however, all studies agree on the higher incidence of blunt abdominal trauma in the civilian population compared to penetrating lesions, which can account for approximately 10 to 30% of abdominal traumatic injuries [7,8]. Penetrating lesions can be stabbed or gunshot in up to 15% of the series [7].…”
Section: Introductionmentioning
confidence: 99%